Urgensi Akta Notaris dalam Pendirian Perseroan Perseorangan Pasca Cipta Kerja - Natyanna, Sheila; Priyono, Ery Agus; Taufiq, Taufiq (Notarius, 2025)
ABSTRACTThe simplification of establishing a Sole Proprietorship Company through the Job Creation Law (UUCK) eliminates the requirement for a notarial deed, creating a problem gap in the form of potential data inaccuracies, unverified documents, and weak legal protection for founders. This study aims to analyze the urgency of notarial deeds in ensuring the legality of Sole Proprietorship Company formation within the electronic registration system. This research employs a normative juridical method using statutory and conceptual approaches, with qualitative descriptive analysis of legal materials. The findings indicate that notaries remain essential to ensuring data validity, legal certainty, and risk mitigation for founders, despite the simplified procedure. Moreover, notaries provide crucial legal guidance to help founders understand their rights, obligations, and liability limits.Keywords: Notarial Deed; Sole Proprietorship Company; Job Creation LawABSTRAKPenyederhanaan pendirian Perseroan Perseorangan melalui UUCK menghilangkan kewajiban akta notaris sehingga menimbulkan problem gap berupa potensi ketidakpastian data, verifikasi dokumen, dan lemahnya perlindungan hukum bagi pendiri. Penelitian ini bertujuan menganalisis urgensi akta notaris terhadap legalitas pendirian Perseroan Perseorangan dalam sistem pendaftaran elektronik. Penelitian menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan konseptual, serta analisis bahan hukum secara deskriptif-kualitatif. Hasil penelitian menunjukkan bahwa peran notaris tetap diperlukan untuk memastikan keabsahan data, kepastian hukum, dan mitigasi risiko bagi pendiri, meskipun proses pendirian telah disederhanakan. Selain itu, kehadiran notaris memberikan edukasi hukum yang penting agar pendiri memahami hak, kewajiban, dan batas tanggung jawabnyaKata Kunci: Akta Notaris; Perseroan Perseorangan; Undang-Undang Cipta Kerja